Green Process of Three-Component Prostaglandin Synthesis and Rapid 11C Labelings for Short-Lived PET Tracers (IntechOpen, 2023)
This book is devoted to highly polished and potentiated novel C couplings developed by our group (M. Suzuki) in the course of a long-term, tight collaboration of chemistry, biology, and medicine experts, focusing on advanced organometallic techniques for the construction of a whole prostaglandin (PG) framework and new methodology for introducing short-lived 11C radionuclide into carbon frameworks. The book is written to attract the interest of scientists working in chemistry and interdisciplinary research areas such as medicinal chemistry, radiochemistry, chemical biology, molecular imaging, and related industries.